Transportasi dan Jaringan Perdagangan Cendana Timor Barat Abad XIX - Mesah, Jeff Wilfred (Historia Madania: Jurnal Ilmu Sejarah, 2025)
The sandalwood trade of the past is an interesting historical study topic to discuss, which is also one of the reasons why this theme is important to raise. Research on the transportation and sandalwood trade network in West Timor in the 19th century aims to reconstruct the historical process that occurred with the sandalwood trade in West Timor, which opened trade routes and networks with other regions in Asia and Europe. The main problem is how the transportation and trade network of West Timor sandalwood in the 19th century when West Timor was under the influence of the Dutch government? This is then explained in several research questions such as who were the main actors involved and what was the transportation model or system in the sandalwood trade in West Timor in the 19th century. To obtain answers to these main questions, a critical history method is used with the use of primary and secondary sources such as archives, journals, reports, photographs, and relevant reference reviews as well as archival analysis and literature studies to complete the data. The stages in this method include heuristics and data verification or source criticism, followed by interpretation and historiography or historical writing. This research found that Dutch government controls, such as shipping taxes, actually led to a decline in the sandalwood trade. Furthermore, local trade, initially conducted by indigenous traders from the Bugis, Makassarese, Javanese, and Chinese, began to be dominated by Chinese traders, while the outbound trade network was dominated by European traders. Similarly, sandalwood transportation and shipment were heavily influenced by West Timor's geography.